THE MARGINALIZATION OF MASS MEDIA TOWARDS WOMEN'S REPORTING (SARA MILLS' CRITICAL DISCOURSE ANALYSIS ON INDONESIAN NEWS): MARGINALISASI MEDIA MASA TERHADAP PEMBERITAAN WANITA (ANALISIS WACANA KRITIS SARA MILLS PADA BERITA INDONESIA) - Baidilah, Anggi; Hamdani, Agus (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This research examines the role of online media in Indonesia in reporting on sexual violence against women. Quality media is expected to present information objectively and in a balanced manner. However, often the news coverage on sexual harassment experienced by women portrays them within a particular narrative. Currently, the exploitation of women takes place through more sophisticated and well-packaged methods, including the discourse expressed in mass media. Women in the media are often visually highlighted but their true meaning is neglected. If this trend continues, the gender gap between women and men will be further reinforced, potentially leading to increased gender oppression with women as the main victims. The problem addressed in this study is the discourse analysis based on Sara Mills' theory. Sara Mills' feminist discourse theory discusses issues related to women, such as how women are portrayed in the news. The research methodology employed in this study is literature review. The research findings conclude that news texts exhibit bias in representing women within the context of sexual harassment across three different media platforms.